Circadian rhythm in negative affect: Implications for mood disorders. (November 2020) - Emens, Jonathan S.; Berman, Alec M.; Thosar, Saurabh S.; Butler, Matthew P.; Roberts, Sally A.; Clemons, Noal A.; Herzig, Maya X.; McHill, Andrew W.; Morimoto, Miki; Bowles, Nicole P.; Shea, Steven A.
Highlights: Mood has a circadian rhythm with the worst mood during the circadian night. Only positive affect has been shown to contribute to this circadian rhythm. It was found that negative affect also has a circadian rhythm that peaks at night. The rhythm in negative affect may have diagnosis and treatment implications for mood disorders. Abstract: In humans, there is an endogenous, near 24-h (i.e., circadian) variation in mood with the best mood occurring during the circadian day and the worst mood occurring during the circadian night. Only positive affect, and not negative affect, has been shown to contribute to this circadian rhythm. We discovered a sharp circadian peak in negative affect during the circadian night coincident with a circadian trough in positive affect. These findings may help explain the association of depression with insomnia, the increased risk of suicide with nocturnal wakefulness, and the correlation between circadian misalignment and symptom severity in Major Depressive Disorder.